2016
DOI: 10.1038/ncomms13292
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of cytosolic Salmonella by caspase-1 and caspase-11 precedes host cell death

Abstract: Sensing bacterial products in the cytosol of mammalian cells by NOD-like receptors leads to the activation of caspase-1 inflammasomes, and the production of the pro-inflammatory cytokines interleukin (IL)-18 and IL-1β. In addition, mouse caspase-11 (represented in humans by its orthologs, caspase-4 and caspase-5) detects cytosolic bacterial LPS directly. Activation of caspase-1 and caspase-11 initiates pyroptotic host cell death that releases potentially harmful bacteria from the nutrient-rich host cell cytoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 66 publications
11
114
1
Order By: Relevance
“…However, others have reported a protective role for caspase-11 during salmonellosis exclusively in the intestine6387. In mouse macrophages or embryonic fibroblasts, both caspase-1 and caspase-11 contribute to cell-autonomous control of intracellular replication of S. Typhimurium and other bacteria2158888990.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have reported a protective role for caspase-11 during salmonellosis exclusively in the intestine6387. In mouse macrophages or embryonic fibroblasts, both caspase-1 and caspase-11 contribute to cell-autonomous control of intracellular replication of S. Typhimurium and other bacteria2158888990.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis mediated by caspase‐11 provides effective host defense against cytosolic Gram‐negative bacteria in vivo . The enzymatic activity of caspase‐11, along with that of caspase‐1, synergistically restricts the growth of intracellular Gram‐negative bacteria in macrophages, intestinal epithelial cells, and fibroblasts …”
Section: Noncanonical Nlrp3 Inflammasomementioning
confidence: 99%
“…A further study has shown that the catalytic activity of caspase-1 and caspase-11 is essential for dampening the intracellular growth of S . Typhimurium Δ sifA (133). In response to infection by L. pneumophila , caspase-11 regulates actin polymerization via cofilin to promote fusion between the vacuole containing L. pneumophila and lysosomes (125).…”
Section: Introductionmentioning
confidence: 99%